All That Is Solid. - Peterson, David (American Sociological Review, 2015)
The belief that natural sciences are more scientific than the social sciences has been well documented in the perceptions of both lay and scientific populations. Influenced by the Kuhnian concept of “paradigm development” and empirical studies on the closure of scientific controversies, scholars from divergent traditions associate scientific development with increased consensus and stability. However, both the macro/quantitative and micro/qualitative approaches are limited in key ways. This article is the first comparative ethnography of a natural science (molecular biology) and a social science (psychology) and it highlights important differences between the fields. Molecular biologists engage in a process of “bench-building,” in which they create and integrate new manipulation techniques and technologies into their practice, whereas psychologists have far less opportunity for this type of development. This suggests an alternative conception of the natural/social divide, in which the natural sciences are defined by dynamic material evolution while the social sciences remain relatively stable.